Green Financing sebagai Instrumen Pemberdayaan Ekonomi Masjid: Analisis Peluang dan Tantangan - Rizka Ar Rahmah; Ar Rahmah, Rizka (Masjiduna : Junal Ilmiah Stidki Ar-Rahmah, 2025)
This study aims to explore the potential of green financing as an instrument for empowering the economic activities of mosques in Indonesia. With the growing awareness of environmental sustainability and the need for economic empowerment, mosques play a strategic role as centers for social and economic activities. This study analyzes the opportunities and challenges of implementing green financing in the context of mosques, using a qualitative approach through in-depth interviews and document analysis. Green financing refers to the funding of projects that support environmental sustainability, such as renewable energy and waste management. In the context of mosques, this can mean investing in solar energy technology, efficient water management, and recycling programs, which not only reduce environmental impact but can also generate additional income and reduce the operational costs of the mosque. The results of the study indicate that green financing can strengthen the economy of mosques through various environmentally friendly initiatives. For example, installing solar panels can reduce electricity costs, while effective waste management can generate income from the sale of recycled materials. However, the study also identifies several major challenges in implementing green financing in mosques. These challenges include a lack of understanding and awareness of the benefits of green financing among mosque administrators and the community, limited human and financial resources to manage green projects, and regulations that do not fully support green financing initiatives in this sector.